Kisah Inspiratif Rosulullah dan Khulafaur Rasyidin Dalam Menjaga Keutuhan dan Persatuan Umat Islam - N, Nurmaini (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Background The life of the Prophet Muhammad SAW is based on a rich and profound story about a man who became a role model for mankind. Muhammad was born in Mecca in 570 AD and grew up in a difficult environment, experiencing loss and hardship from an early age. However, his noble qualities such as honesty, wisdom, and compassion for others formed a strong personality and became the foundation of future leadership. As a prophet, Muhammad received revelations from Allah which later became the foundation of Islamic teachings. The exemplary behavior and positive values of the Khulafaurrasyidin are very important in developing Muslim character. The exemplary behavior of the Khulafaurrasyidin is a reference or source for Muslims in developing good character and behavior according to Islamic teachings.